KKN-Thematic Program Higher Education Seminar in The Middle of Job Competition at SMK Muhammadiyah 01 Pasuruan - Sofiyatul Widat; Octavia Zuroidhah Annah; M. Rizky Oktavian; M. Alfarizi M. Alfarizi; Yudi Hari Rayanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2022)
This Education Seminar Program aims to provide an introduction to SMK students regarding the importance of continuing higher education at the lecture level in the era of the industrial revolution 4.0 which is an era where the need for knowledge and technology is developing very rapidly which then results in various rapid and competitive changes as well as in human life the application of artificial intelligence is one of the characteristics of the era of the industrial revolution 4.0. The main support regarding the occurrence of the era of the industrial revolution 4.0 is the world of education where many students and students in Indonesia have been able to operate cellphones and gadgets as their main needs in supporting their daily activities besides gadgets, supported by a good internet network, of course they can surf the international world using the results of technological advances in the Era of the industrial revolution 4.0. The world of education is required to be able to create learning that supports the development of students to be able to keep up with the development of information and communication technology at the present time where it is the main capital to face challenges in the world of work after the completion of the education period where competition in the world of work is currently increasingly competitive.